Regulation of gene expression during DNA damage response in Plasmodium falciparum - Gupta, Devendra Kumar (2016)
The genomic integrity of Plasmodium parasite remains under constant threat from exogenous and endogenous genotoxic stresses throughout the developmental stages of the parasite complex life cycle. Here, we investigated the responses of P. falciparum to DNA damaging agents to assess its DNA repair capacity on one side and the mutational effect of DNA damage on the other. Using DNA microarrays, we have characterized a global transcriptional response of P. falciparum to methyl methanesulphonate (MMS), which alkylates DNA bases and causes strand breaks. Alongside, we studied the epigenetic regulation of DNA damage response in the parasite. Our results showed that MMS causes up-regulation of DNA repair and DNA repair-related pathways. MMS-induced gene expression is accompanied by hyperacetylation of histone lysine residues H4K8Ac, H4K16Ac and deacetylation of H3K56Ac and H3K9Ac. Intriguingly, the induction of the DNA repair machinery, initially observed in the drug susceptible parasite strains (3D7 and D6), could not be detected in two drug-resistant parasites (Dd2 and W2). Also, our genome sequencing results identified point mutations in 18 DNA repair genes that were exclusively present in Dd2 and W2. These latter strains were previously shown to exhibit a mutator phenotype also termed as accelerated resistance to multiple drugs (ARMD). Although a link between the DNA repair machinery and ARMD phenotype has been suggested previously, our results provide mechanistic evidence that the ARMD phenotype is potentially caused by a defect in a sensing/signaling pathway(s) that triggers the DNA repair machinery upon DNA damage. Further, Artemisinin, the primary antimalarial drug for P. falciparum infections, has been long debated for its mechanism of action. Here, we elucidated that MMS and artemisinin induced transcriptional up-regulation of repair machinery and altered the chromatin structure in a similar manner at multiple stages. Taken together, artemisinin elicits DNA damage response in parasite, which is similar to the MMS mediated response. Differential gene expression in Plasmodium confers flexibility to the changing environments as well as providing the parasite with indispensable tools for survival and pathogenesis. The exact mechanism of such transcriptional differences in Plasmodium gene expression is unknown. Although few focused studies on sub-telomeric virulence gene families have indicated the role of chromatin in regulating the differential gene expression. Our objective was to investigate the role of epigenetic mediated mechanism in the differential gene expression in two P. falciparum strains. By comparing the gene expression and histone modification patterns (H3K9Ac and H3K56Ac) between Dd2 and T996 strains, we found that most differentially expressed genes associated with differential H3K56 acetylation. Further, we characterized one of the AP2 domains containing transcription factor (putative), PF14_0271, which was found to be both differentially acetylated and differentially expressed between P. falciparum strains. Using endogenous tagging and knock-out approach, our results suggest that PF14_0271 is a schizont specific transcriptional regulator.